The impacts of ocean acidification, warming and their interactive effects on coral prokaryotic symbionts - Jinlong Li; Guangjun Chai; Yilin Xiao; Zhiyong Li (Environmental Microbiome, 2023)
Abstract Background Reef-building corals, the foundation of tropical coral reefs, are vulnerable to climate change e.g. ocean acidification and elevated seawater temperature. Coral microbiome plays a key role in host acclimatization and maintenance of the coral holobiont’s homeostasis under different environmental conditions, however, the response patterns of coral prokaryotic symbionts to ocean acidification and/or warming are rarely known at the metatranscriptional level, particularly the knowledge of interactive and persistent effects is limited. Using branching Acropora valida and massive Galaxea fascicularis as models in a lab system simulating extreme ocean acidification (pH 7.7) and/or warming (32 °C) in the future, we investigated the changes of in situ active prokaryotic symbionts community and gene expression of corals under/after (6/9 d) acidification (A), warming (H) and acidification–warming (AH) by metatranscriptome analysis with pH8.1, 26 °C as the control. Results A, H and AH increased the relative abundance of in situ active pathogenic bacteria. Differentially expressed genes (DEGs) involved in virulence, stress resistance, and heat shock proteins were up-regulated. Many DEGs involved in photosynthesis, carbon dioxide fixation, amino acids, cofactors and vitamins, auxin synthesis were down-regulated. A broad array of new DEGs involved in carbohydrate metabolism and energy production emerged after the stress treatment. Different response patterns of prokaryotic symbionts of massive G. fascicularis and branching A. valida were suggested, as well as the interactive effects of combined AH and persistent effects. Conclusions The metatranscriptome-based study indicates that acidification and/or warming might change coral’s in situ active prokaryotic microbial diversity and functional gene expression towards more pathogenic and destabilized coral-microbes symbioses, particularly combined acidification and warming show interactive effects. These findings will aid in comprehension of the coral holobiont’s ability for acclimatization under future climate change.